PENGARUH MEDIA PENDINGIN (COOLANT) DAN GEOMETRI PAHAT POTONG TERHADAP TINGKAT KEKASARAN DAN MAKROSTRUKTUR PADA PEMBUBUTAN RATA MEMANJANG BAHAN BAJA EMS-45 (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
EMS-45 steel is a type of steel that can be categorized as medium grade steel, which is often applied in the field of industry in various fields of industry. Lathe is a process of forming a workpiece both metal and non metal by reducing the previous size to a specified size. The purpose of this study is to determine the effect of the use of cooling media and chisel geometry on the conventional process of welding and macro photo structure.The method used is the experimental method. Variations used are without cooling medium, 20w50 oil, pure dromus oil without mixture of water and water from faucet, while variation of chisel geometry ie chisel A: cutting angle 10 °, free corner 8 °, 12 ° exhaust corner, chisel B: Cutting angle 12 °, free angle 9 °, 15 ° exhaust angle, and chisel C: cutting angle 13 °, free angle 10 ° and 20 ° exhaust angle. After variation treatment on the lathe process, then tested the level of surface roughness and macro photo structure on each specimen. The analysis used is descriptive statistic.Test results yield roughness and macro structure values. The lowest roughness value was obtained in the 5th specimen by 3.18 μm with the N7 roughness and the highest roughness obtained on the 11th specimen at 6.08 μm with the N8 roughness. The macro picture of the structure is most visible on the 5th specimen and the most distant look is on the specimen 11. So it can be concluded that the maximum roughness level that can be obtained from the chime geometry tolerance rate is at its middle value and without using cooling medium.